Pengaruh Electronic Word Of Mouth (EWOM) Dan Pengetahuan Halal Terhadap Minat Beli Produk Kosmetik Halal Di Shopee - Adek Safitri; Muhammad Isa; Idris Saleh (WELFARE: Journal of Islamic Economics and Finance, 2025)
The development of technology has changed people's consumption views on trends and lifestyles, which is a major driver of the growth of the cosmetics market including the purchase of halal cosmetics. This is due to the emergence of e-commerce such as shopee which provides buying and selling services for all products including halal cosmetics. However, with this convenience, it problems that make some consumers not interested in buying halal cosmetics. This happened to female students of the ITKESSU. With background as student Islam, she should prefer products from the level of halalness. Student comes from a health school where health always coincides with the halalness of a product. This is indicated by the BPOM evidence and halal logo on a product indicates that the product is safe to use and guaranteed halal. It turns out that the problems that arise are caused by E-WOM and halal knowledge which have a significant effect on buying interest in halal cosmetics in shopee. The purpose of this study is to identify whether these factors, namely EWOM and halal knowledge, influence buying interest in halal cosmetic products. This research uses a quantitative approach. The results is indicate that electronic word of mouth and halal knowledge have a positive and significant effect on buying interest in halal cosmetic products in shopee.